Discrete wavelet analysis to assess long-term trends in geomagnetic activity - Zossi Artigas, Marta Maria (2006)
To assess long-term trends in geomagnetic activity, the discrete wavelet transform using the Daubechies function was applied to aa and Dst for periods 1868–2003 and 1957–2003 respectively.Among a variety of techniques available for analysing trends, wavelet analysis has emerged in the last decade as a useful statistical tool for this purpose. The wavelet order and border conditions of the transform were selected minimizing the mean relative error. A sequence of alternating trends is obtained in the case of aa, with the greatest minima around 1880 and 1905 followed by 1965 and 2000. Maximum values occur around 1890, 1955 and 1990. Dst index shows the last two minima and the maximum around 1990. Long term trends in solar wind velocity, density and pressure, IMF magnitude B, southward component Bz, sunspot number Rz and the coronal index were also analysed in order to identify possible causes for the observed long-term variation in geomagnetic activity. They all qualitatively agree with aa and Dst behavior pointing out a solar origin.ior pointing out a solar origin.